Kompetensi Penyuluhan Petugas Promosi Kesehatan di Wilayah Kabupaten Sidenreng Rappang - Sunandar Said; Zulkarnain Sulaiman; Devy Febrianti; Mardhatillah Mardhatillah (Jurnal Kesehatan Pertiwi, 2020)
Introduction: There is a lack of health center staff with a background in health promotion, so that officers with different educational backgrounds are appointed to become health extension officers with the consideration that they are participating in training as health educators. Purpose: This study aims to elaborate the Extension Competencies of Health Promotion Officers in the City of Makassar. Methods: This study uses qualitative research with a case study approach. The research informants were 10 people. Data collection techniques using in-depth interviews, document review and observation. Results: (1) The ability to analyze targets and determine priorities for health promotion officers is still limited. (2) The ability to determine the identity of health promotion officers varies. (3) The ability to implement extension services for health promotion officers is good. (4) The ability to determine the method of counseling for health promotion officers is good (5) The ability to evaluate the extension of promotion officers is still limited to seeing feedback or asking directly about the objectives to evaluate extension activities Conclusion: Conclusion: The ability to analyze targets or determine priorities, determine identity and evaluate outreach activities for health promotion officers still needs to be improved. Meanwhile, the ability of the media / extension tools and methods of extension are good.